Scarabaeidae (Coleoptera) na Caatinga baiana: Distribuição e Planejamento de pesquisas - Campos, Elkiaer Moraes (2012)
The Caatinga is the main biome in the Brazilian Northeast region, occupying an area of about 735,000 km², and suffering with the process of human disturbance from the beginning of its colonization to-day, which in recent decades has resulted in an accelerated process of desertification and loss of biodiversity. Based on this scenario, the objective of this work is to systematize the information on Scarabaeidae in the caatinga of Bahia State looking for a research strategy for the group. In order to reach this goal we used entomological collections information altogether with zoological surveys in various areas of caatinga in the state, and analyzed for Scarabaeidae composition and richness; through the use of species distribution modeling techniques for analysis of environmental similarities we propose a research design for the group. We recognized 81 species that come from 27 locations, with approximately 60% of them in unique occurrences; we also found relationships between Scarabaeidae species and the physiognomic types of caatinga. The similarity analysis showed a trend of environmental preference Scarabaeidae for the eastern region toward the south and also west-northwest region. Finally we generated a map indicating high priority areas for future research on Scarabaeidae in the caatinga of Bahia.